(untitled) (Review of Croatian History, 2022)
This work is based on the analysis of the register of baptisms and weddings of the Desne parish in the Neretva Valley. Godparents’ and wedding witnesses’ relationships were analysed, godparents’ for 1870 and 1871, and wedding witnesses’ for the period from 1870 to 1875. By analysing the data, it was tried to be determined whether those relationships were used as social network links or as a means of better positioning within the community. The study is based on the analysis of the number of godparents and their sex structure, on the interval between the birth of the children and their baptism, on the correspondence of the children’s and godparents’ names and surnames, on the number of multiplied godparents, on the comparison between the godparents’ and children’s parents’ jobs as well as on the places where children and godparents lived. In the case of weddings, the number and sex of wedding witnesses, correspondence of the children’s and wedding witnesses’ names and surnames, multiplied wedding witnesses’ and the places where spouses and wedding witnesses lived were analysed.